Recent Trends of Gram-negative Bacteremia in a State of North India, the Forthcoming Challenges IGMC Shimla, India - Katoch, Pankaj; Kanga, Anil (Innovations in Microbiology and Biotechnology Vol. 3, 2022)
Background: Vascular endothelial dysfunction plays a critical role in the evolution of sepsis there is an increase in vascular permeability leading to coagulation abnormalities and subsequent dysfunction of major organs [1]. Bloodstream infections(BSI) are a cause of life-threatening complications in all age groups of the population especially the extreme age groups who are very much prone to the risk. BSIs have also been associated with increased rates of hospitalization, increased length of stay, and increased hospital costs and are a financial burden on the patient and their families. Antibiotic usage is associated with bacteremia, septicemia, and mortality through many factors. We are aware that Gram-negative bacteria due to many causes are becoming increasingly resistant to the currently used antimicrobial therapy. Here, in this study, we report the incidence and etiology and of the Gram-Negative bacterial isolates and their clinical significance from our tertiary care institute located in the Northern part of India. Materials and Methods: Prospective Observational Study conducted in the Department of Microbiology IGMC Shimla for a tenure of one year to determine the incidence and etiology of Gram-negative bacterial isolates and their antimicrobial resistance profile. All the blood culture blood culture was observed in the Bactec bd fx system for at least 5 days before they are reported as sterile. Results: Among the total 1275 cultures which were positive for bacteria, 931(73.02%) were positive for Gram-negative bacteria. Among the total of 931culture that were positive for Gram- negative bacteria, The Non-fermenter group of organisms was isolated in 292(31.36%) cultures, followed by E. coli 266(28.57%). Among the total of 931 cultures positive for GNB, a maximum of 335 (35.98%) belonged to 0-1 year. Among them, 574 (61.65%) were males while 357 (38.35%) were females. Conclusion: Nonfermenter group was the commonest organism among Gram-negative isolates. Infants were more commonly positive as compared to another age group. Males were more commonly culture positive as compared to females among gram-negative isolates.